Proteomic analysis of field cancerization in pharynx and oesophagus: a prospective pilot study - Roesch Ely, Mariana; Leipold, Alexandra; Nees, Matthias; Holzinger, Dana; Dietz, Andreas; Flechtenmacher, Christa; Wolf, Thomas; Zapatka, Marc; Bosch, Franz X. (The journal of pathology, 2010)
‘Field cancerization’ in head and neck squamous cell carcinoma (HNSCC) is poorly understood and it may extend from the pharynx into the oesophagus. Both local recurrences and second primary carcinomas/second field tumours may originate from field cancerization. Our prospective pilot study aimed at the identification of patients suffering from field cancerization on the basis of mucosal protein profiles. Five mucosal biopsies from the oropharynx, hypopharynx and from three regions of the oesophagus were taken from 24 patients. Protein profiles were generated from the mucosal biopsies. After classifier learning, using the profiles of the patients without tumour diagnosis (n = 9), we were able to discriminate between the different mucosal sites and between healthy mucosa and HNSCC using tumour and healthy tissue samples. Mucosal biopsies of tumour patients (n = 15) revealed changes in the protein profiles similar to those in the tumours. During 42 months median follow-up, six tumour patients experienced local recurrences and second field tumours, of which three occurred in the oesophagus. In all six cases, tumour relapse was correctly predicted by altered mucosal protein profiles (p = 0.007, Fisher's exact test, two-tailed). Consequently, molecular field cancerization had a strong impact on progression-free survival (p = 0.007, log-rank test). Protein profiles of small diagnostic biopsies hold great promise to improve personalized risk assessment in HNSCC. Larger studies are needed to further substantiate these findings. Copyright © 2010 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.